Pengaruh Pemberian Insentif, Pengawasan Kerja & Motivasi Kerja Terhadap Prestasi Kerja Pegawai PT. Armada Bandar Bangun Persada - Erita Erita; Honest Radiansyah; Jefry Kasdi; Yafi Kurniawan; Aziz Surya Patih (Sekolah Tinggi Maritim Yogyakarta, 2021)
This study aims to analyze 1) the effect of incentives partially on work performance, 2) effect supervision partially on work performance, 3) the effect of working motivation partially on work performance, 4) the effect of incentives, supervision and motivation, simultaneously against work performance of employees in the Office of PT.Armada Bandar Bangun Persada. The results of data analysis showed that (1) there is a significant effect of incentives on job performance, tcount 2.818> 1.986 ttabel; (2) a significant difference between the oversight of the performance, with thitung 3,269> t table 1.986 (3) there is a significant relationship between motivation for work performance, tcount 2,332> 1,986 ttabel; (4) a significant difference between providing incentives, supervision and motivation on work performance with 16.060> Ftabel 3.10. The amount of incentives, supervision and motivation on work performance is 35.1% and the remaining 64.9% is influenced by other factors not included in this study.